2022
DOI: 10.1002/ardp.202100412
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, in silico ADMET, docking, and antiproliferative evaluations of [1,2,4]triazolo[4,3‐c]quinazolines as classical DNA intercalators

Abstract: Eleven novel [1,2,4]triazolo [4,3-c]quinazolines were designed, synthesized, and evaluated against HepG2 and HCT-116 cells. The molecular design was performed to investigate the binding mode of the proposed compounds with the DNA active site. The data obtained from biological testing highly correlated with that obtained from molecular modeling. HCT-116 was found to be the most sensitive cell line to the influence of the new derivatives. In particular, compounds 6 f and 6 e were found to be the most potent deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In continuance of our earlier works in the scope of the design and syntheses of novel anticancer medicines [36][37][38][39][40][41][42][43][44], particularly VEGFR-2 inhibitors [45][46][47][48][49][50][51][52][53][54], thiazolidine-2,4-diones bearing sulfonylthiourea moieties were synthesized to obtain the four keys of VEGFR-2 inhibitors pharmacophoric features (Figure 3) [55][56][57]. The focus of the current study was to utilize the lead modification approach for sorafenib, a potent VEGFR-2 inhibitor, to obtain novel potent inhibitors.…”
Section: As Anticancer Agentsmentioning
confidence: 70%
“…In continuance of our earlier works in the scope of the design and syntheses of novel anticancer medicines [36][37][38][39][40][41][42][43][44], particularly VEGFR-2 inhibitors [45][46][47][48][49][50][51][52][53][54], thiazolidine-2,4-diones bearing sulfonylthiourea moieties were synthesized to obtain the four keys of VEGFR-2 inhibitors pharmacophoric features (Figure 3) [55][56][57]. The focus of the current study was to utilize the lead modification approach for sorafenib, a potent VEGFR-2 inhibitor, to obtain novel potent inhibitors.…”
Section: As Anticancer Agentsmentioning
confidence: 70%
“…to the docking algorithm's capability to obtain the reported binding mode of sorafenib via binding with Cys917 in the hinge region and Glu883 and Asp1044 in the DFG-binding domain (Figure 8). [46,54] The docking results demonstrated that the synthesized compounds were able to detect the VEGFR-2 kinase ATP binding site and interact with the critical amino acids in the same way that sorafenib does. The binding free energies are summarized in Table 6.…”
Section: Gene Expression Analysis For Bax Bcl-2 and Caspase-3mentioning
confidence: 93%
“…For the synthesis of the target compounds, the reactions sequence is illustrated in Schemes 1 and 2. According to the literature, [45,46] the commercially available 2-aminobenzoic acid 1 was fused with urea 2 at 200°C for 6 h to get quinazoline-2,4-dione 3. Chlorination of compound 3 was proceeded using phosphorous oxychloride and TEA to afford 2,4dichloroquinazoline 4.…”
Section: Chemistrymentioning
confidence: 99%
“…Depending on the mentioned facts, and the extension of producing new anti-cancers 30–36 , especially that intercalators for DNA 21–24 , 37–40 , it was reported herein modifications of EAPB0203 through hybridisation with privileged heterocyclic fragments as potent anticancer agents against MCF-7, HepG2 and HCT-116. Inhibition of DNA topoisomerase II, induction of apoptosis, cell cycle arrest, and inhibition of cancer cell proliferation are the main hallmarks applied to estimate potent chemotherapies for their anticancer activities 41 .…”
Section: Introductionmentioning
confidence: 99%